ANALISIS KESALAHAN LOGIKA DALAM DISKUSI SISWA SEKOLAH DASAR - Gio Mohamad Johan (Jurnal Tunas Bangsa, 2019)
The general objective of this study is to describe Indonesian language errors in the discussion process of sixth grade students of SDN 1 Galagamba. The specific purpose of this study is to describe logical errors in the discussion process sixth grade students of VI SDN 1 Galagamba students. This study uses descriptive research methods. The source of the data in this study were the sixth grade students of SDN 1 Galagamba, Ciwaringin Subdistrict, Cirebon Regency. The instruments used in this study were observation sheets and oral data recording devices. Data collection uses non-test techniques such as recording, recording, and observation. The data analysis technique uses qualitative data analysis techniques. Based on the results of the analysis of the discussion process of sixth grade students of VI SDN 1 Galagamba students found 15 logical errors. The whole logic error in this case is caused by students' illogical statements so that the meaning is difficult. The meaning of the sentence tends to be unreasonable. Abstrak Tujuan umum penelitian ini adalah mendeskripsikan kesalahan berbahasa Indonesia dalam proses diskusi siswa kelas VI SDN 1 Galagamba. Adapun tujuan khusus penelitian ini yakni, mendeskripsikan kesalahan logika dalam proses diskusi siswa kelas VI SDN 1 Galagamba. Penelitian ini menggunakan metode penelitian deskriptif. Sumber data dalam penelitian ini adalah siswa kelas VI SDN 1 Galagamba Kecamatan Ciwaringin Kabupaten Cirebon. Instrumen yang digunakan dalam penelitian ini yakni lembar observasi dan alat perekam data lisan. Pengumpulan data menggunakan teknik nontes seperti rekam, catat, dan observasi. Teknik analisis data menggunakan teknik analisis data kualitatif. Berdasarkan hasil analisis terhadap proses diskusi siswa kelas VI SDN 1 Galagamba ditemukan sebanyak 15 kesalahan logika. Keseluruhan kesalahan logika dalam hal ini disebabkan karena pernyataan siswa yang tidak logis sehingga maknanya yang sulit dinalar. Makna dari kalimat tersebut cenderung tidak masuk akal. Kata Kunci: Logika, Siswa, Sekolah Dasar